Spectrum occupancy measurement: a case for cognitive radio network in lagos, Nigeria - Paulson, E. N. (Asian Research Publishing Network, 2017)
The proliferation in technologies and with the recent introduction of new paradigm for wireless communication, the demand for wireless devices has increased drastically in recent years. This therefore, posed a major threat on the available frequency spectrum and as a result, an efficient method for the utilisation of the limited frequency spectrum is required. As the scarcity of frequency spectrum is a major problem in the telecommunication field, cognitive radio technology has been identified as a promising solution to this problem. Cognitive radio allows the opportunistic access of licensed bands by unlicensed users without causing harmful interference to the licensed user. There is a need to evaluate the utilisation level of the licensed bands in order to identify which frequency bands can be used for cognitive radio implementation. Nevertheless, spectrum measurement campaigns have been conducted mostly in USA and a few other locations around the world. In this paper, the results of the measurement campaign conducted in Ikeja, the capital city of Lagos, Nigeria covering the range of frequency 700 MHz up to 2.2 GHz is presented. The measurement results are analysed and compared to the frequency allocation table published by the Nigerian Communications Commission. The results obtained show that the frequency spectrum is underutilised and therefore a significant amount of spectrum is available for the future implementation of cognitive radio networks.